(untitled) (XXI Century. Spanish Literature and Culture, 2012)
The object of this study is describing the narrative mechanism of two bimedial short short stories by J.M. Merino which include a manipulated painting (“Nighthawks” vs “Las Meninas”). The study aims to explain why the manipulation provides, in one case, an imaginative reading (complementary story) and, in the other, an analytical-reflective one.